Pengaruh Konformitas Terhadap Perilaku Narapidana Dalam Pembinaan Kerohanian Agama Islam - Faula A Fajrin; Padmono Wibowo (Indonesian Journal of Social Science Education (IJSSE), 2022)
spiritual development at the Class II A Purwokerto Penitentiary by taking a sample of 87 respondents by spreading questionnaires at random. The analysis of this study using IBM SPSS Statistics 21 was conducted against conformity variables (x) and inmate behavior variables (y). From the results of calculations that the t test (signification) is obtained the result that the value of t calculates >t table (4.211 > 2,007) with a signification ratio of 0.000<0.05 or in other words that H0 is accepted and H1 is rejected. The results showed the percentage of influence given by conformity variables to the behavior of inmates conducted a determination test where in the test obtained the number R square of 0.524.This shows the magnitude of the influence caused by variable conformity as a free variable has an effect of 52.4% on the variable Behavior of Prisoners as bound variables, the remaining 47.6% is another factor that is not studied by researchers. So it can be concluded that there is a positive and very significant relationship between conformity to the behavior of inmates in Lapas Class II A Purwokerto.